In between: Time and self evaporations during quarantine - Tragou, Elena (Homo Virtualis, 2020)
This pandemic forced upon us a change in our work and life habits. As all professionals in the mental health area, I started working from home, using digital platforms for online psychotherapy sessions. That helped me and my clients stay connected, strengthening our sense of synergy, alliance and care. As confidentiality and safety protocol issues remained intact, I was feeling more at ease with internet use, embracing the digital world and concentrating on my therapeutic work. As that was happening, my therapeutic relational choices took an uncommon turn, bringing forth some interesting creative work between my clients and myself. I started feeling “in between”, as if my sense of self was evaporating in time and space, flirting around with a freshly emerged sense of intra- and inter-connections. This vignette outlines how this trancestic experience unfolded and how much intrapsychic travelling took place with zero tolerance to physical or social distance.